(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Posterior Reversible Encephalopathy Syndrome is a rare and acute neuro-radiological entity, characterized by several symptoms of different aetiologies. The main etiologies of PRES are HTN, Pre-eclampsia, Eclampsia, Immunosuppressive therapy etc, but there are many unexplained causes too. Here we report a case of post-partum woman who developed PRES in post-operative period, who was complicated by the postdural puncture headache following spinal anesthesia- a rare and uncommon etiology. J Bangladesh Coll Phys Surg 2017; 35(1): 43-45